Does the Accuracy and Repeatability of Refractive Error Estimates Depend on the Measurement Principle of Autorefractors? - Padhy, Debananda; Bharadwaj, Shrikant R.; Nayak, Suryasmita; Rath, Suryasnata; Das, Taraprasad (Translational vision science & technology, 2021)
The purpose of this study was to determine the accuracy and repeatability of refractive errors obtained using three autorefractors based on different measurement principles, vis-à-vis, gold-standard retinoscopy. Accuracy of noncycloplegic, sphero-cylindrical refractive error of 234 eyes was obtained using the rotary prism-based RM-8900 closed-field autorefractor, photorefraction based Spot vision screener, wavefront aberrometry based E-see, and streak retinoscopy by four different examiners, masked to the results of each other. Intersession repeatability of autorefractors was determined by repeat measurements in a subset of 40 subjects. Retinoscopy values of M, J , and J power vectors for the cohort ranged from -10.2 to 8 D, -1.4 to 1.8 D, and -0.9 to 1.2 D, respectively. Across autorefractors, the interequipment bias of M and J power vectors were statistically insignificant (< ±0.5 D; > 0.05) but the corresponding limits of agreement were ±2.5 and ±1 D, respectively, without any trend across instruments or the patient's age ( > 0.5). Repeatability of M and J power vectors were ±0.75 D and ±0.40 D, respectively, across autorefractors. The range of J power vector was too narrow for any meaningful analysis. Refractive errors measured using autorefractors operating on different principles show minimal bias and good short-term repeatability but relatively large agreement limits, vis-à-vis, retinoscopy. Among them, the wavefront aberrometry based E-see autorefractor performs relatively better in all measurement parameters evaluated here. Although autorefractor estimates of noncycloplegic refractive error appears independent of their measurement principle, their relatively poor agreement with gold-standard retinoscopy warrants caution while used for screening and quantification of refractive errors.